Efficient Photoelectrochemical Reduction of CO2 on Pyridyl Covalent Bonded Ruthenium(II) Based-Photosensitizer. (20th October 2016) - Liu, Jibo; Shi, Huijie; Huang, Xiaofeng; Shen, Qi; Zhao, Guohua
Graphical abstract: Highlights: High total faradic efficiency of PEC CO2 conversion was obtained on Ru-Py. The catalytic activity of pyridyl for CO2 reduction was well retained. The C-C single bond linkage in Ru-Py facilitates methanol production. The intermediate pyridiumformate was proved by the simulated reaction. Abstract: Photo/electrochemical CO2 reduction using pyridine was feasible to produce methanol via the formation of pyridiniumformate intermediate. To improve the reduction efficiency, a pyridyl bonded ruthenium (II)-based photosensitizer catalyst (Ru-Py) was designed for photoelectrochemical CO2 conversion. The photocurrent density on Ru-Py modified electrode in CO2 saturated solution was 0.103 mA cm −2 higher than that without illumination. The total Faradaic efficiency (f) reached 83.1%, whereas the turnover number (TON) for methanol was 38.4 in aqueous solution after 8 h irradiation. The methanol production was 24.1 μmol which was higher than the published literatures (less than 8 μmol) in similar systems could be attributed to the efficient electron transfer between the photosensitizer and the pyridyl active site covalently linked by C-C bond, as well as the strong and wide absorption up to 610 nm resulted from the large conjugated structure of the ligands. The mechanism investigation revealed that the N atom in pyridyl as catalytic active sites played significant role in CO2 conversion by forming the pyridiniumformate intermediate which was confirmed by the simulation reaction. Meanwhile, in order to realize the reduction process intuitively, the density functional theory (DFT) was applied to simulate the structure of Ru-Py and the pyridiniumformate intermediates.